Absolute autonomy, respectful recognition and derived dignity: Towards a typology of meaningful work. (2nd December 2021) - Laaser, Knut; Bolton, Sharon
Abstract: Theoretical and empirical contributions to meaningful work (MW) have flourished in the last two decades; investigating how the interplay of organizational factors with employee attitudes and experiences enables or denies MW. This paper reviews MW literature in the fields of management and organizational behaviour, political philosophy, the humanities and sociology with the aim of identifying and comparing conceptualizations of MW and how they relate to low‐skilled work. The review illustrates that a wide range of MW concepts either interpret low‐skilled work as bereft of essential sources for MW, or focus exclusively on workers' innate drive to make meaningful experiences and thereby neglect the politics of working life. Making the point that low‐skilled work can also be meaningful, the paper develops a framework for low‐skilled work that has at its heart the interplay between the unique characteristics and dynamics of the labour process and workers' agential responses. The framework rests on a combination of labour process analysis and industrial relations approaches, along with sociological concepts of agency. It develops three interdependent conceptual dimensions of core autonomy, respectful recognition and derived dignity that aim to capture MW in low‐skilled work settings. The framework contributes to vibrant debates in the MW literature by showcasing how meaningfulness emerges through bottom‐up collective and individual practices, relations and strategies that are reflective of the formal structures, demands and relations of low‐skilled work.